The Importance of Moral Education In the Life of Islamic Society - Sudiran, Sudiran; Ahriani, Ahriani (International Journal on Advanced Science, Education, and Religion, 2025)
Moral education is the core of Islamic teachings that aims to form individuals who are faithful, pious, and have noble character. In the life of Islamic society, moral education plays a role as a moral foundation that creates social harmony, improves the quality of individuals, and strengthens Islamic brotherhood. This article discusses the importance of moral education, the challenges in its implementation, and strategic solutions to integrate moral values ​​in the life of Islamic society. The results of this study indicate that moral education has a significant impact on building a peaceful, moral, and prosperous society.